THE DYNAMICAL BEHAVIOUR OF THE DOUBLE - SHOES BRAKE USED IN ELEVATORS - Bolat, Berna; Bogoclu, Muharrem E. (YILDIZ TECHNICAL UNIV, 2016)
The double-shoe braking system used in elevators of buildings with the purpose of mechanical braking behavior are used an experimental method for the preparation of the dynamic model in this study. The double-shoe braking system is used in many mechanisms. The double -shoe braking system is a complex structure consisting of many parts, so that it is difficult to create a model with a theoretical approach to make the right contact definitions. Therefore, experiments were performed by creating experimental model in this study and the results of these experiments have shown that the structural noise and vibrations were significantly affected by the speed, and braking and take-off acceleration of the engine.
Keywords: Elevators; elevator safety systems; double-shoe brakes; vertical transportation systems; FRICTIONAL NOISE; GENERATING MECHANISM; SURFACE-ROUGHNESS; SQUEAL NOISE; WEAR; Engineering